A Novel Algorithm for Big Data Clustering - Gujare, Vishal Kumar; Malviya, Pravin (International Journal of Computer Sciences and Engineering, 2025)
Now a day, large amounts of heterogeneous digital data is available this big data need to be carefully examined for analysis point of view. Big data is nothing but a large volume of heterogeneous and distributed data collection. In real world big data applications has contain huge amount of continuously grow able data but it is very costly to clean up, extract , manage and process data using present software tools. Fast and accurate retrieval of the relevant information from dataset has always been a significant issue. Prominent and accurate data clustering is a main task of exploratory data analysis and data mining applications. Clustering process is one of the data mining techniques for dividing informative dataset into group and it is a kind of unsupervised data mining technique.